2021
DOI: 10.4103/1735-3327.324020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of at-home and in-office bleaching and three composite types (hybrid, microhybrid, and nanofilled) on repair shear bond strength of aged composites

Abstract: Background: Only a few controversial studies have assessed the repair bond strength of a fresh composite to aged composite. Moreover, no studies exist on repair bond strength of fresh composites to bleached composites. Therefore, this preliminary study was conducted to assess repair shear bond strength (SBS) of three composites bonded to nonbleached and at-home and in-office bleached composites. Materials and Methods: In this experimental in vitro study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…A significant reduction in the bond strength of freshly added composite to the bleached one was noticed in this study between the 3 tested groups and the control one. This result was in covenant with Zakavi et al [20] who concluded that a major reduction of the bond strength occurred between the bleached composite and the freshly added one upon using of a nanofilled type while an acceptable bond strength was noticed upon using hybrid and microhybrid composite resin.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A significant reduction in the bond strength of freshly added composite to the bleached one was noticed in this study between the 3 tested groups and the control one. This result was in covenant with Zakavi et al [20] who concluded that a major reduction of the bond strength occurred between the bleached composite and the freshly added one upon using of a nanofilled type while an acceptable bond strength was noticed upon using hybrid and microhybrid composite resin.…”
Section: Discussionsupporting
confidence: 78%
“…These results may be referred to the using of certain whiting material and also the different method of bleaching. Zakavi et al [20] described that no major disturb of the bond strength between freshly added composite to a bleached preexisted composite.…”
Section: Discussionmentioning
confidence: 99%